Serum Lipoprotein(a) Level and Apolipoprotein B/A1 Ratio in Patients of Hemodialysis and Peritoneal Dialysis: A New Approach to Predict Cardiovascular Risks in Chronic Kidney Disease - Feroz, Salahuddin; Md Salahuddin, Abu Zafor; Russel, Md Al Rizwan; Islam, Rafi Nazrul; Mozaffor, Miliva; Selim, Md Shahidul Islam (Bangladesh Critical Care Journal, 2020)
Background: Serum lipoprotein(a) and Apolipoprotein B/A1 ratio are new, independent cardiovascular risk factors in patients on dialysis. Conversely, the choice of dialysis procedure influences the uremic dyslipidemia in chronic kidney disease (CKD) patients. Objective: To compare lipoprotein(a) levels and apolipoprotein B/A1 ratio in patients of chronic kidney disease (CKD) stage 5 undergoing hemodialysis or peritoneal dialysis. Methods: This cross-sectional study was conducted in Department of Nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from September 2016 to March 2018. A total of 55 CKD stage 5 patients were included in the study – 31 in hemodialysis (HD) (group A) and 24 in continuous ambulatory peritoneal dialysis (CAPD) (group B). Group A patients were on low flux dialysis with bicarbonate dialysate 4 hours twice weekly dialysis with unfractionated heparin as anti-coagulant with a dialysis adequacy (Kt/V) >1.2. Group B patients were on 3 exchanges over 24 hours with 2 litres of 1.5% glucose fluid with a weekly measured Kt/V >1.7. Serum levels of Lipoprotein(a), Apolipoprotein B/A1 ratio were measured in both groups by using the standard laboratory technique. Results: In group A, most of the patients were in 31-50 years age group (45.1%), while in group B, majority belonged to >50 years age group (54.16%). Patients’ gender showed a male predominance in both groups, i.e. 54.83% and 70.83% respectively. Most of the patients were from urban areas, i.e. 87.1% and 70.8% group A and B respectively. Dialysis adequacy (Kt/V) was found 1.46 for HD patients (group A) and 1.81 for CAPD patients (group B). Dyslipidemia was evident more in CAPD patients than HD patients, as per raised serum Lipoprotein(a) level (83.3% vs 74.1%) and raised Apolipoprotein B/A1 ratio (100% vs. 77.4%). Moreover, comparing with HD patients, CAPD patients showed increased level of serum Lipoprotein(a) (41.4±23.5 mg/dl vs 37.4±25.3 mg/dl; p>0.05) and Apolipoprotein B/A1 ratio (1.59±0.24 vs 1.04±0.22; p<0.001). Conclusion: The maintenance CAPD treatment is associated with more pronounced alterations of the lipoproteins and lipid metabolism than those observed during HD treatment. Besides, serum lipoprotein(a) level and apolipoprotein B/A1 ratio were found simple, accessible and effective markers of dyslipidemia in both groups. Bangladesh Crit Care J September 2020; 8(2): 91-95